KONSEP PENDIDIKAN SEUMUR HIDUP DALAM PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - Syaifuddin Zuhri; Mudhofar Mudhofar (JURNAL PUSAKA, 2014)
Education is a human universality as well as a most strategic factor in his life. In the framework of philosophy, man is a material object, while the formal object is all efforts striven for the development of all the potency, all of which were directed at achieving a particular goal. Human existence should be clearly drafted to obtain the ideal formulation of education.Human existence has been equipped with a variety of useful basic potency by God as a tool to reveal the explicit reality that surrounds them in order to get to the truth. As the only creature that has the ability of orientation in three dimensions of time (past, present, and future) make human being special among other beings. To maintain the credibility of the self, man must keep learning. Given by nature not as a mere creature in â€œbeingâ€ but rather a creature of â€œbecomingâ€, he requires a learning process continually, continuously as well sustainably throughout his life, ranging from cradle to grave. This then produced the paradigm of life-long education.Islam, so many centuries ago before the passing of Western concept, has had a theory about lifelong education. Even Islamic education is not only oriented towards the anthropological dimension, but rather includes two poles at once; namely the theocentric and anthropocentric.This study basically aims to explore the concept of lifelong education philosophically, including: (1) what is the nature of lifelong education?; (2) how is the development of lifelong education?; (3) how is the implementation of lifelong education? To answer these questions, this library research uses hermeneutics to interpret facts, data, and phenomena. The collection of data is obtained from primary sources and secondary ones with deductive and inductive approaches. This study also uses reflective contextual logic, namely a system of reasoning with governance between the empirical and the abstract.Keywords: lifelong education, learning process, human potency